PENGARUH KUALITAS AUDIT (UKURAN KAP), PROFITABILITAS, DAN UKURAN PERUSAHAAN (SIZE) TERHADAP OPINI AUDIT GOING CONCERN (OAGC) PADA SEKTOR TEKNOLOGI DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Raja Salomo Sianturi; Jhon Rinendy (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The primary objective of this research is to explore the relationship between audit quality, profitability, firm size, and the issuance of going-concern audit opinions. To achieve this goal, a sample of 13 technology firms listed on the Indonesian Stock Exchange between 2019 to 2021 was collected using purposive sampling. The collected data was then analyzed using the logistic regression analysis method with the help of the SPSS application. The study found that neither audit quality nor profitability has a significant effect on the issuance of going-concern audit opinions. However, the research indicates that firm size plays a crucial role in determining the likelihood of receiving a going-concern audit opinion. In other words, larger companies are more likely to receive such opinions than smaller firms.